Sulfated glycosaminoglycans in human vocal fold lamina propria - Park,Sung Woo (2017)
Abstract Introduction: The distribution, concentration and function of glycosaminoglycans in the various vocal fold tissues are still unclear. Objective: To evaluate the distribution and concentration of sulfated glycosaminoglycans in different layers of the human vocal fold according to gender and age. Methods: We used 11 vocal folds obtained from cadavers (7 men and 4 women) with no laryngeal lesion, less than 12 h after death, and aged between 35 and 98 years. The folds underwent glycosaminoglycans extraction from the cover and ligament, and post-electrophoresis analysis. Data were compared according to the layer, age and gender. Results: The concentration of dermatan sulfate was significantly higher in all layers. No differences were observed in the total concentrations of glycosaminoglycans in layers studied according to gender. It is significantly lower in the cover of individuals aged below 60 years. Conclusion: Dermatan sulfate, chondroitin sulfate, and heparan sulfate were observed in the human vocal folds cover and ligament of both genders, with the concentration of dermatan sulfate being significantly higher in all layers. Glycosaminoglycans concentration on the cover is significantly lower in individuals below 60 years compared with elderly.